Characteristics, 3M Behavior, and Climate Factors with Cases of Dengue Heart Fever (DHF) in Indonesia (Literature Review 2015-2021) - Franky Darmawan; Lilis Sulistyorini; H. J Mukono; Soedjajadi Keman; Yudied Agung Mirasa (Journal of Health Science and Prevention, 2023)
Dengue Hemorrhagic Fever (DHF), has become the fastest growing Vector Borne disease (VBD) in the world over the last few decades, with an increase of 30 times. This study aims to analyze the relationship between the characteristics, behavior of 3M, and climate factors with cases of Dengue Hemorrhagic Fever (DHF) in Indonesia. This research was conducted using a literature review method. The research was conducted online by taking research objects in English and Indonesian journals that discussed cases of DHF in Indonesia. The sample used was appropriate and determined in this study totaling 45 research articles. The results showed that men were more likely to be infected with DHF because they were more active outside the home. The age prone to DHF is the age under 16 years old, or the toddler, child, and early teens. The education of the head of the family is also an important factor in efforts to control the dengue outbreak. The results of the literature review show that the characteristics have a significant relationship with dengue cases. Not all people are aware of the importance of 3M behavior, seen from the proportion of people who apply 3M less than people who apply 3M. 3M's behavior is a factor that can reduce the occurrence of dengue cases. Stakeholders or policy makers in the health sector, especially those in charge of controlling the dengue outbreak, should take the results of this study into consideration in determining regulations or policies related to dengue outbreak control.